Alleviation of bovine serum albumin on the neurotoxicity of silver nanoparticles in zebrafish (Danio rerio) larvae - Yan, Zhenhua; Chen, Yufang; Yang, Yuqiong; Zhou, Yixin; Su, Pengpeng; Yuan, Saiyu (Frontiers in Marine Science, 2024)
Silver nanoparticles (AgNPs) are ubiquitous in the aquatic environment and have attracted extensive attention to their toxic effects on aquatic species. However, responses of the nervous system to AgNPs are little known, especially co-existing with the ubiquitous natural organic matter (NOM), which is critical for the ability to act in aquatic species. Here, this study investigated the neurotoxicology of environmentally relevant AgNPs with or without bovine serum albumin (BSA; a classical NOM) to zebrafish (Danio rerio) using visualized transgenic zebrafish. Exposure to AgNPs reduced the locomotor behavior of zebrafish by 28%–45%, including swimming distance and velocity, exhibiting obvious behavioral inhibition. The visualized transgenic zebrafish treated with AgNPs showed developmental retardation in the early development of the heart, central nervous, and motor nerve, as well as the related neurodevelopment genes, which may be responsible for the lowered locomotor behavior. In addition, AgNPs can specifically interfere with the cholinergic system and affect neuronal signaling, ultimately leading to behavioral abnormalities. However, the co-existing BSA alleviated the neurotoxicity of AgNPs in zebrafish, which may partially be attributed to the increased size and electronegativity of AgNPs caused by BSA, thus reducing the direct interaction of AgNPs with cells. The interaction between BSA and the released Ag+ from AgNPs may also be responsible for the alleviation of the neurodevelopment dysfunction in zebrafish. These findings provide valuable insights into the toxicity and risks of AgNPs in natural aquatic environments.